2018
DOI: 10.1161/jaha.118.009223
|View full text |Cite
|
Sign up to set email alerts
|

Slow Potential at the Entrance of the Slow Conduction Zone in the Reentry Circuit of a Verapamil‐Sensitive Atrial Tachycardia Originating From the Atrioventricular Annulus

Abstract: BackgroundSlow conduction zone in a verapamil‐sensitive reentrant atrial tachycardia originating from atrioventricular annulus is composed of calcium channel–dependent tissue. We examined whether there was a slow potential (SP) at the entrance of the slow conduction zone.Methods and ResultsWe first identified the pacing site from where manifest entrainment and orthodromic capture of the earliest atrial activation site were demonstrated in 40 atrioventricular annulus patients with atrioventricular annulus. Radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
5
1
Order By: Relevance
“…Most of the patients in this study (133 of 145 (92%)) had reentrant tachycardias as a mechanism of PSVT, such as AVNRT (77) and AVRT (51), including 5 patients with perinodal ATP‐sensitive AT of which the mechanism is supposed to be reentry 12,20 . Based on our results, it appears that PSVT with reentrant mechanism also have preserved inducibility under deep sedation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Most of the patients in this study (133 of 145 (92%)) had reentrant tachycardias as a mechanism of PSVT, such as AVNRT (77) and AVRT (51), including 5 patients with perinodal ATP‐sensitive AT of which the mechanism is supposed to be reentry 12,20 . Based on our results, it appears that PSVT with reentrant mechanism also have preserved inducibility under deep sedation.…”
Section: Discussionmentioning
confidence: 63%
“…In patients with AT, the earliest activation site indicated by electroanatomical mapping was targeted for ablation. As for perinodal ATP‐sensitive AT of which the mechanism is considered to be macro‐reentry, ablation was tried at the reentrant site outside of Koch's triangle first, and then the earliest activation site was targeted 11,12 . Either of non‐irrigated or irrigated catheters were used in AVRT and AT ablation by physician choice, with maximum power up to 35 W.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, SKYLINE demonstrated the underlying AT mechanism was localized reentry and highlighted the successfully ablated site, located 8 mm away from the EAAS, showing a low amplitude and fractionated potential, consistent with a previous report. 9 These findings indicate that the effective ablation site for the AVN-AT is the exit site of the SCZ, as highlighted by the LUMIPOINT. The distance between the successfully ablated site and HB was also similar to previous findings.…”
Section: Discussionmentioning
confidence: 85%
“…A previous study demonstrated that the atrial electrogram at the successfully ablated site appeared 15 ms later than the HB electrogram during AVN-AT. 9 This delay in electrogram detection is attributed to the low amplitude of the electrogram, which may not be accurately detected by the ablation catheter. Additionally, the annotation algorithm of LUMIPOINT software, which is unique and unlike any other 3D mapping systems, helps to identify the mechanism of this arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Yamabe et al . [ 86 ] have described low-frequency, late potentials following local atrial activation during sinus rhythm, probably reflecting a delayed activation of the tachycardia origin, near the site of successful ablation, in patients presenting with atrial tachycardia originating from the tricuspid annulus. The presence of these potentials suggests a slowly conducting, common arrhythmogenic substrate of these tachycardias.…”
Section: Av Ring Tachycardia Hypothesismentioning
confidence: 99%